Impact of temporomandibular joint disorders on body posture - Mielcarek, Magdalena; Złotnicka, Katarzyna; Jaranowska, Katarzyna; Borek, Joanna Monika; Malak, Roksana Ewa; Samborski, Włodzimierz (Journal of Education, Health and Sport, 2019)
Introduction: Occlusion defects, temporomandibular joints disorders, and postural defects often occur in pediatric patients. The temporomandibular joint disorder is a term that includes a range of clinical complaints of masticatory muscles, temporomandibular joint, and related structures. They can lead to incorrect spinal positioning in the cervical spine, which may result in body posture defect. Aim: Review of literature to determine the relationship between temporomandibular joint disorders and postural defects in children. Material and methods: The PubMed, Research Gate and Google Schoolar databases were reviewed using the keywords: (temporomandibular joint, malocclusion), (postural defect). The authors have analyzed articles published in the last 5 years. Results: A forward shift of the body posture due to head protraction, increased cervical lordosis, deepening of lumbar lordosis and thoracic kyphosis occurs in malocclusion class II according to Angle’a scale. This defect affects the location of the center of gravity of the body, which is shifted forward, which causes impairment of gait stability. Whereas class III malocclusions present a shifted posture backward. These defects can cause pain in given structures. The relationship between malocclusion and postural defects can be related to speech defects. Conclusions: Available literature shows that the temporomandibular joint affects body posture. Temporomandibular joint dysfunction can affect the position of the shoulders, spine, pelvis, and limbs. It is necessary to conduct further research on this topic.